Multi‐microRNA diagnostic panel for heart failure with preserved ejection fraction in preclinical and clinical settings - Reza Parvan; Natale Rolim; Andreas B. Gevaert; Alessandro Cataliotti; Emeline M. vanCraenenbroeck; Volker Adams; Ulrik Wisløff; Gustavo Jose Justo Silva; the OptimEx Study Group (ESC Heart Failure)
Abstract Aims Heart failure with preserved ejection fraction (HFpEF) is a complex syndrome accounting for half of heart failure cases. Although natriuretic peptides are the most accepted and extensively used biomarkers for heart failure, their diagnostic accuracy for HFpEF remains debatable. Here, we aimed to identify a panel of circulating microRNAs (miRNAs) as potential novel biomarkers for diagnosis of HFpEF in a preclinical model, subsequently validated in human HFpEF patients. Methods and results In a female hypertension‐induced HFpEF model [Dahl/Salt Sensitive (DSS) rats], circulating miRNA levels were screened in the plasma via real‐time quantitative polymerase chain reaction. DSS rats exhibited HFpEF features as indicated by diastolic dysfunction and adverse cardiac remodelling when fed a high‐salt (8%) diet (n = 11) compared with a low‐salt (0.3%) diet (n = 15). A panel of four circulating miRNAs (rno‐let‐7b‐5p, rno‐let‐7e‐5p, rno‐miR‐21‐5p and rno‐miR‐140‐3p) were found significantly altered in the DSS plasma. Clinical performance of miRNA expression analysis was assessed in publicly available datasets of human heart failure patients, including assessment of discrimination of different categories of heart failure [GSE53437; control = 30, heart failure with reduced ejection fraction (HFrEF) = 41, HFpEF = 19] and gender differences (GSE104150; female = 6, male = 10). The miRNA panel significantly discriminated HFpEF patients from healthy individuals and HFrEF patients. We also found significant downregulation of let‐7b‐5p and miR‐21‐5p in females compared with males, regardless of health status. Conclusions A panel of four circulating miRNAs was differently expressed in female HFpEF rats and significantly discriminated HFpEF patients from healthy individuals and HFrEF patients. This cross‐species and bench‐to‐bedside approach demonstrates the potential of miRNA‐based panels for HFpEF diagnosis.